Research and development of a mathematical model of a polymer-based viscous non newtonian fluid for oil and gas wells drilling - Rymchuk, D. V.; Shevchenko, N.; Tulska, Alona Gennadiivna; Ponomarenko, V.; Shudryk, O. (VÚRUP, 2022)
Analysis of the use of biopolymers in drilling and well stimulation for oil and gas production has been performed. Normal Newtonian fluid model, taken used as a sample, is considered a nonlinear viscous fluid. Models that are most common in oil and gas industry are considered. Laboratory studies of rheology of an aqueous solution with various concentrations of xanthan gum have been carried out. An analysis of experimental and numerical hydrodynamic studies in flexible pipes of coiled tubing units has been performed considering the rheology of drilling fluid. For the numerical simulation of the hydrodynamics of a non-Newtonian fluid authors apply an open integrable platform OpenFOAM.
Keywords: non newtonian fluid; polymers; drilling; flushing